The ironic apocalypse in the novels of Leopoldo Marechal - Cheadle, Norman, 1953- (Tamesis, 2000)
Leopoldo Marechal has become a chosen precursor of many contemporary Argentine writers, cineastes, and intellectuals, and so his novels - universally recognized but rarely studied - demand treatment from a contemporary critical sensibility. This study departs from the line of criticism that reads Marechal as a Christian apologist, arguing instead that Marechal's 'metaphysical' novels are really metafictional, ludic exercises informed by ironic scepticism.
Keywords: Marechal, Leopoldo, -- 1900-1970 -- Criticism and interpretation.; Marechal, Leopoldo, -- 1900-1970; Politics in literature.; LITERARY CRITICISM -- American -- Hispanic American.; Politics in literature; Criticism, interpretation, etc.